UK multicenter retrospective comparison of novel active versus conventional passive fixation coronary sinus leads. (5th August 2020) - Gerontitis, Dimitrios; Diab, Ihab; Chow, Anthony W. C.; Hunter, Ross J.; Leyva, Francisco; Turley, Andrew J.; Williams, Ian; Ullah, Waqas; ,
Abstract: Background: A novel active fixation coronary sinus (CS) lead, Attain Stability (AS), has been released aiming to improve targeted lead positioning. Rather than being wedged into the distal vessel, it relies on a side helix for fixation. We aimed to compare implant procedure parameters and electromechanical stability of the AS lead with passive CS leads. Methods: A retrospective study involving six major UK cardiac centers. Patients who received active fixation leads were compared with passive fixation lead recipients in a 1:2 ratio. The primary outcome was total lead displacements (combined macrodisplacement/microdisplacement, defined as displacements requiring repositioning procedures, an increase in threshold ≥0.5 V or pulse width ≥0.5 ms, or a change in pacing polarity). Results: A total of 761 patients were included (253 AS leads and 508 passive fixation leads), of which 736 had follow‐up data. The primary endpoint rate was 31% (75/241) in the active and 43% (214/495) in the passive group ( p  = .002). Six patients (2.5%) in the active group and 14 patients (2.8%) in the passive group required CS lead repositioning procedures ( p  = 0.981). On multivariable analysis, active leads were associated with a reduction in lead displacements, odds ratio 0.66 (95% confidence interval: 0.46–0.95), p  = .024. There were differences in favor of passive leads in procedure duration, 120 (96–149) versus 127 (105–155) min ( p  = .008), and fluoroscopy time, 17 (11–26) versus 18.5 (13–27) min ( p  = .0022). The median follow‐up duration was similar (active vs. passive): 31 (17–47) versus 34 (16–71) weeks, ( p  = .052). Conclusion: AS CS leads had improved electromechanical stability compared with passive fixation leads, with only minimal increases in implant procedure and fluoroscopy times.